SOCIO-PSYCHOLOGICAL FACTORS OF EMOTIONAL RELATIONS IN THE PEDAGOGICAL COMMUNITY - Botirova Yorqinoy (American Journals Publishing, 2024)
Emotional relations within the pedagogical community play a vital role in creating a supportive and conducive learning environment. This article examines the socio-psychological factors that influence emotional relations among educators, including trust, communication, collaboration, job satisfaction, and organizational culture. It explores how these factors impact the overall well-being and effectiveness of the pedagogical community. The article highlights the importance of fostering positive emotional relations and provides recommendations for improving interpersonal dynamics within the pedagogical community. By understanding and addressing these socio-psychological factors, educational institutions can cultivate a harmonious and collaborative environment that benefits both educators and students.
Keywords: Emotional relations, pedagogical community, socio-psychological factors, trust, communication, collaboration, job satisfaction, organizational culture.